Enhancement of Villa Vänern -Achieving the grade GOLD in the Swedish environmental classification system Miljöbyggnad - Månsson, Tommie; Johansson, Jesper (My University, 2013)
Villa Vänern is a 120 m2, two stories villa. It comes in three different types: detached house, row house and terraced house. Peab is one of the Nordic countries largest construction company and has recently made a decision that all of their self-developed projects are to be certified according to the demands of the environmental certification system Miljöbyggnad. Miljöbyggnad is built up of 15 indicators, which are categorized into 11 aspects. The aspects are graded and combined into three area grades, which are Energy, Indoor climate and Materials and chemicals. An earlier study shows that Villa Vänern achieves the grade SILVER as a final grade in Miljöbyggnad. Peab is now interested to see how can Villa Vänern be developed to get GOLD on all criteria’s in Miljöbyggnad. The measurable indicators that don’t meet the annual energy usage of 82,7 kWh/m2, the design heating power demand of 29,89 W/m2, solar heat gain and the thermal climate during winter and summer. The solar heat gain and the thermal climate is room dependent and vary in the different rooms. The enhancement of Villa Vänern made in this report consists of changing the orientation of the building, upgrading the window with a more energy efficient glazing unit and frame, suggesting solar shading, adding one layer of insulation in the wall and at last reducing the temperature set points from 22-25°C to 20-26°C. The analysis made in this report shows that it is possible to enhance Villa Vänern to achieve GOLD on all indicators in Miljöbyggnad with quite small measures. A cost estimation together with Peab shows that if around 49 000 SEK is invested in Villa Vänern it achieves the grade GOLD. The changes to the enhanced Villa Vänern are thought through so the occupants have the same or a better living quality in the building after the changes has been made.
Keywords: Energi; Byggnadsteknik; Hållbar utveckling; Building Futures; Energy; Building engineering; Sustainable Development; Building Futures